Changes in the critical erosion velocity for sediment colonized by biofilm - Fang, Hongwei; Shang, Qianqian; Chen, Minghong; He, Guojian (Sedimentology, 2014)
In flowing water the incipient motion of sediment can be affected by the presence of microbial biofilm growth. This article documents a series of flume experiments using non‐uniform sediments, in which sediment entrainment was investigated for cases where the sediment was immersed in deionized water, so that no biofilm developed, and for cases where a bio‐sediment was cultivated by placing the sediment in a mixture of natural water and nutrient solution. Differences in entrainment and the velocity at incipient motion were measured over an eight week period, as biofilm grew. It was found that the incipient motion phenomena were quite distinct between the two kinds of sediment. Sediment with biofilm was more stable and, over time, incipient velocity increased to a threshold level, before declining. Biofilm development is clearly an important control on the stability of sediments, especially in eutrophic water bodies. Two incipient velocity formulas were derived for sliding and rolling conditions. Film water theory was utilized to describe the cohesive force between sediment particles and the adhesive force generated by biofilm was introduced into the formula derivation; the time variation characteristics of biofilm strength and the features of the substrate were also taken into consideration. Such analyses can help to predict sediment transport changes due to biofilm presence in nutrient‐rich water bodies.